In Vitro Activities of Enantiopure and Racemic 1′-Acetoxychavicol Acetate against Clinical Isolates of Mycobacterium tuberculosis - Warit, Saradee (Sci Pharm, 2017)
In the process of evaluating the effect of several plant extracts against Mycobacterium tuberculosis using the Microplate Alamar Blue Assay (MABA), an extract of Thai herb Alpinia galanga rhizome and its major component, 1′-acetoxychavicol acetate (ACA), exhibited marked anti-tuberculosis activity. The minimal inhibition concentrations (MICs) of the S-enantiomer of ACA (S-ACA) against M. tuberculosis H37Ra ATCC 25177 and H37Rv ATCC 27294 strains were 0.2 µg/mL and 0.7 µg/mL, respectively. More than 95% of 100 drug-sensitive and 50 drug-resistant mycobacterial clinical isolates were inhibited by extracted S-ACA at 1.0 µg/mL. All of the remaining isolates were inhibited at 2.0 µg/mL. In contrast to the S-enantiomer, synthetic racemic 1′-R,S-ACA (rac-ACA) showed MICs of 0.5 µg/mL and 2.7 µg/mL for M. tuberculosis H37Ra ATCC 25177 and H37Rv ATCC 27294, respectively, suggesting that the anti-tuberculosis effect might be primarily due to the S-form. These observations were in line with the MICs of rac-ACA against 98% of 93 drug-resistant clinical isolates, which showed the effective inhibitory dose at 2.0 µg/mL. After exposure to 2.7 µg/mL of rac-ACA for at least 3 h, the tubercle bacilli were completely killed. These demonstrated that ACA had potent anti-TB activity.